Indigenization for development the case of Southeast Asia - CPA Research team (1984)
The process of indigenization of public administration technology for development necessitates an examination of (1) the socio-cultural-historical conditions of a developing country and (2) the native characteristics and institutions that promote or hinder national development. In this context, the experience of five Southeast Asian nations, i.e., Indonesia, Malaysia, Thailand, Singapore and the Philippines, in two areas, namely, their civil service systems and their rural development programs, are analyzed. Whether the source of technology is Western or Asian, the interest of the nation should be the primary consideration.
Keywords: Indigenization -- Southeast Asia; Administrative reform -- Southeast Asia; Civil service -- Southeast Asia; Rural development -- Southeast Asia